2015
DOI: 10.2147/vmrr.s71402
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam sedates Passeriformes for field sampling but affects multiple venous blood analytes

Abstract: Feasibility and effect of midazolam administration on blood analytes and for sedation of Passeriformes being collected in a larger study of genetic biodiversity was assessed. Midazolam (5.6±2.7 mg/kg) was administered intranasally prior to sampling, euthanasia, and specimen preparation of 104 passerine birds. Each bird was assessed for sedation score and then multiple analytes were determined from jugular blood samples using the i-STAT® point of care analyzer at “bird side”. Most birds were acceptably sedated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
4
9
0
Order By: Relevance
“…A small sample size from the western population and inherent analyte variability likely prevented statistical distinctions between the western and hybrid zone populations (Table 3). The difference in glucose east and west of the BE was also observed in our related studies of multiple Texas passerine species [29,30]. Although pO 2 and sO 2 also differed between titmice east and west of the BE, differences resulted from age, sex, and/or midazolam administration.…”
Section: Location and Rainfall Increase Venous Blood Glucose Concentrationssupporting
confidence: 78%
See 4 more Smart Citations
“…A small sample size from the western population and inherent analyte variability likely prevented statistical distinctions between the western and hybrid zone populations (Table 3). The difference in glucose east and west of the BE was also observed in our related studies of multiple Texas passerine species [29,30]. Although pO 2 and sO 2 also differed between titmice east and west of the BE, differences resulted from age, sex, and/or midazolam administration.…”
Section: Location and Rainfall Increase Venous Blood Glucose Concentrationssupporting
confidence: 78%
“…Since this hybrid zone occurs at a strong ecotone, we aim to investigate which blood gases and electrolytes differ between Tufted and Black-crested Titmice and assess if the differences are linked to climate and/or habitat. In a previous study of a suite of passerines, including titmice, we observed differences in venous blood analytes between individuals sampled east of the BE, relative to those sampled west of the BE [29,30]. We hypothesize that, between species, differences in blood analyte concentrations will be strongly correlated with habitat or climatic differences associated with the different ecoregions east and west of the BE.…”
Section: Texas Hybrid Zonementioning
confidence: 88%
See 3 more Smart Citations